Mitochondria-Targeted Mesoporous Organic Silica Nanoplatforms for Overcoming Cisplatin Resistance by Disturbing Mitochondrial Redox Homeostasis - Lv, Bin; Ma, Jingru; Wang, Yumeng; Qu, Xinyu; Qiu, Junjun; Hua, Keqin (Frontiers in Chemistry, 2022)
Cisplatin (also known as DDP) resistance is one of the biggest challenges in the treatment of ovarian cancer. Recent studies have found that mitochondrion, as a potential target of DDP, participates in drug-related apoptosis and resistance. Overexpressed glutathione (GSH) in resistant cells is involved in protecting mitochondria from DDP or DDP-induced ROS. In this work, triphenylphosphonium (TPP) modified disulfide bond-rich (S-S) mesoporous organic silica nanoplatforms (DMON) were developed to deliver DDP (TPP-DMON@DDP) to mitochondria for overcoming DDP resistance. TPP supported the migration of nanoplatforms to the mitochondria, with consequent depletion of mitochondrial GSH by the S-S bond of DMON, leading to mitochondria in redox dyshomeostasis. These treated cells seemed more susceptible to the DDP released from the nanoplatforms. Significantly increased ROS production, mitochondrial damage, and apoptosis were observed in TPP-DMON@DDP-treated cells. Overall, interference of mitochondrial redox homeostasis provides a new opportunity for improving DDP cytotoxicity against resistant cells.